Nef-induced CCL2 Expression Contributes to HIV/SIV Brain Invasion and Neuronal Dysfunction - Lehmann, Michael H.; Lehmann, Jonas M.; Erfle, Volker (Frontiers in Immunology, 2019)
C-C motif chemokine ligand 2 (CCL2) is a chemoattractant for leukocytes including monocytes, T cells, and natural killer cells and it plays an important role in maintaining the integrity and function of the brain. However, there is accumulating evidence that many neurological diseases are attributable to a dysregulation of CCL2 expression. Acquired immune deficiency syndrome (AIDS) encephalopathy is a severe and frequent complication in individuals infected with the human immunodeficiency virus (HIV) or the simian immunodeficiency virus (SIV). The HIV and SIV Nef protein, a progression factor in AIDS pathology, can be transferred by microvesicles including exosomes and tunneling nanotubes (TNT) within the host even to uninfected cells, and Nef can induce CCL2 expression. This review focuses on findings which collectively add new insights on how Nef-induced CCL2 expression contributes to neurotropism and neurovirulence of HIV and SIV and elucidates why adjuvant targeting of CCL2 could be a therapeutic option for HIV-infected persons.